Distribution and abundance of microplastics in coastal sediments depends on grain size and distance from sources. (November 2021) - Marques Mendes, A.; Golden, N.; Bermejo, R.; Morrison, L.
Abstract: Microplastic deposition in marine sediments is a geographically widespread problem. This study examines microplastics in intertidal and subtidal sediments at 87 locations in habitats designated as Special Areas of Conservation (SACs) and Special Protection Areas (SPAs) on the coastline of Ireland. Established methodological approaches including, organic matter digestion, density separation, particle extraction and polymer identification were applied. Microplastic abundance was closely related with distance from known sources and concentrations were greater in intertidal as opposed to subtidal sediments. Colourless, polyethylene fibres and polypropylene fragments were the most abundant MP recorded and finer grained sediments were shown to entrap more MPs than coarser sediments. The results demonstrate that an understanding of potential sources of pollution, sediment type and hydrodynamic conditions are very important in terms of MP abundance and distribution in marine sediments and also in terms of effective waste management strategies and policy aimed at reducing the global plastics problem. Graphical abstract: Unlabelled Image Highlights: Microplastic concentrations greater in intertidal versus subtidal sediments Finer grain sediments entrap more microplastics than coarser grained sediments. Colourless, polyethylene fibres and polypropylene fragments were the most abundant. Distance from source and sediment type are key factors for distribution of MPs.